PENGARUH GREEN MARKETING, DAN BRAND IMAGE TERHADAP REPURCHASE INTENTION YANG DIMEDIASI KEPUASAN KONSUMEN(STUDI PADA FAST FOOD TOP BRAND 2022) - Haiatin Jamiilah, (2022)
This study uses a quantitative method with the aim of proving the influence of Green Marketing and Brand Image both directly and indirectly on Repurchase Intention which is mediated by the variable Consumer Satisfaction. This study used 100 respondents from consumers of Fast-Food Top Brand 2022 restaurants in DKI Jakarta as primary data, and secondary data researchers obtained through various references related to the research. Data were collected using purposive sampling techniques and analyzed using descriptive and inferential analysis techniques with the help of SmartPLS software. So that data processing obtains the results that (1) Green Marketing has a positive and significant effect on Repurchase Intention, (2) Brand Image has a positive and significant effect on Repurchase Intention, (3) Green Marketing has a positive and significant effect on Consumer Satisfaction, 4) Brand Image has an effect positive and significant effect on consumer satisfaction, 5) consumer satisfaction has a positive and significant effect on repurchase intention.